Research In Creating Artworks – Comparison 3 Case Studies of Fine Art Creative Process - Octalyna Puspa Wardany (IJCAS (International Journal of Creative and Arts Studies), 2016)
In fine arts, creating artworks need doing research. The research has many types. Mostly, it is not the scientific research type. But, nowadays, scientific research is commonly implementing in creating artworks too. It is important to know the various researchs in creating artworks, so it could be able to understand how research has the significant role in creating artworks. This study examines the research in creating artworks through comparation of 3 case studies of fine art exhibitions; (1) the creative process of water color painting exhibition Climen by Surya Wirawan in 2012 which the process held for 4 years (2008-2012), (2) the painting exhibition Melupa by Ugo Untoro in 2013 which the process held for 13 years (2000-2013), (3) the art project Tentang Hutan by gerimisUngu Production 2014 which the process held for 4 years (2011-2014). Each of those 3 creative process has different type of research, methods, and period, artworks as the output, experience of the artist whom get involved, and certain location in Indonesia. These 3 case studies describe that the research in creating artworks can be scientific with fully consideration, or semiscientific in consideration, or unscientific between consideration and uncosideration. And, the certain research implemented in creating artworks is related to the artist (individual and cultural), purpose of the artworks and exhibition, and content of the artworks which appointed.